An investigation of verbal interaction between teacher and students in teaching English as a foreign language - Saragih, Mandra; Nissa, Khairun; Saragih, M. Afiv Toni Sehendra (JEES (Journal of English Educators Society), 2023)
The study of verbal interactions between teachers and students in English foreign language classes focuses on understanding the dynamics and communication patterns that occur during the language teaching and learning process. The current study reveals the issues about investigating types of verbal interaction realized by an English teacher and students in the classroom and also investigating its impact on students’ speaking achievement. Forty-three students of the grade VII-3 of MTS Negeri 3 Medan and one English teacher participated in this study. The data was probed through classroom observation, recording the teaching classroom interaction. The finding exposed that firstly, teacher talk was dominantly practiced English in the teaching classroom interaction rather than students’ talk. Secondly, the types of verbal interaction that occurred in the teaching classroom interaction by which realized by an English teacher were: 1. Asking Questions interaction 33%, 2. At lecturing classroom interaction 9%, 3. Giving Direction interaction 11%. The total percentages of all types of scores are about 53%. The types of verbal interaction that were applied by the students as follows; 1. The students’ talk responses 23%,2. The students’ talk initiation10% by which accumulated about 33%. They were 14 percent of students not giving any feedback (Silence). The speaking score at final test showed that 34.88% or 15 students who were able in verbal interaction between teacher and students. Consequently, this scholarly paper also provides advice on English teacher to highlight effective teaching practices and provide insight into how language learning can be enhanced through meaningful and engaging interactions. HIGHLIGHTS: Teachers most often use six different approaches: accepting feelings, praising and encouraging, using students' ideas, posing questions, lecturing, and providing instructions. The English teacher is advised to expand the intensity of students verbal interactions in learning English with the teacher and among students in the classroom. The teacher-talk control had a high rate of classroom involvement. It indicates that teacher spends significant time controlling